E-043 Intradural or Extradural? A role for High Resolution MRI and Intracranial Aneurysms. (14th July 2013) - Walsh, K; Bain, M; Hui, F
Abstract : Introduction: High Resolution post contrast Magnetic Resonance Imaging has been used to evaluate vessel walls in atherosclerotic disease as well as vasculitides in order to characterise wall thickness and enhancement. High resolution magnetic resonance imaging may also be useful in characterising aneurysms by identifying regions of all thickening which may have implications for microsurgical repair, such as in giant aneurysms where wall thickening at the neck may impede exclusion of the aneurysm sac from the circulation. Increased visiblity of the cavernous sinus and dura may also help better localise paraclinoid aneurysms. Methods: High resolution Magnetic imaging was performed in 18 patients harbouring intracranial aneurysms and results were reviewed and observations correlated. Patterns of enhancement in normal vessels were also assessed by experienced neuroradiologists in order to form a baseline for image interpretation. Results: Of 18 HRMR exams of aneurysms, 5 were paraclinoid, 2 were thrombosed large aneurysms, 3 were fusiform aneurysms, 7 were intradural aneurysms (MCA 2, PCOM 1, ACOM 4) and one dolichoectatic vessel. In the paraclinoid aneurysms, relationship to the cavernous sinus and dura helped localise the aneurysm as intra or extradural. Conclusion: In vivo imaging of aneurysm walls may help in treatment planning by both localisation and identification of wall characteristics that may hinder surgery or stable coiling. Further research is necessary. Disclosures: K. Walsh: None. M. Bain: None. F. Hui: 3; C; Microvention, Penumbra.